Floculação: Considerações a partir da análise clássica e da avaliação direta da distribuição de tamanho de partículas - Moruzzi, Rodrigo Braga [UNESP]; de Oliveira, André Luiz; De Julio, Marcelo; Dutra, Ricardo Henrique de Andrade; da Silva, Pedro Augusto Grava [UNESP] (FapUNIFESP (SciELO), 2016)
This article presents some considerations on the flocculation from the classical analysis and direct evaluation of the particle size distribution. For this purpose, essays in bench scale were performed. The results were evaluated in the light of classical approach, given by the dimensionless number Camp (GT) and the kinetics of aggregation and breakage, as well as particle size distribution. It has been found that the use of GT isolated product is not suitable to represent the variations in flocculation performance and the classical model of aggregation and break-up can be biased by an indirect measurement of turbidity and sedimentation as an intermediate step. On the other hand, the direct evaluation of performance by particle size distribution, represented by linear continuous function, can be a promising tool for the evaluation of flocculation.
Flocculation: Considerations from the classical analysis and from direct evaluation of particle size distribution
Keywords: Aggregation and breakage; Camp number; Flocculation; Particle size distribution